2004
DOI: 10.1162/089892904322755610
|View full text |Cite
|
Sign up to set email alerts
|

Neural Substrates of Response-based Sequence Learning using fMRI

Abstract: Abstract& Representation of sequential structure can occur with respect to the order of perceptual events or the order in which actions are linked. Neural correlates of sequence retrieval associated with the order of motor responses were identified in a variant of the serial reaction time task in which training occurred with a spatially incompatible mapping between stimuli and finger responses. After transfer to a spatially compatible version of the task, performance enhancements indicative of learning were on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
93
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 41 publications
13
93
2
1
Order By: Relevance
“…Given that the implicit group learned both location and action sequences, it is surprising that the explicit-locations group did not demonstrate learning the sequence of actions. This result conflicts with previous research that has demonstrated that explicit knowledge does not interfere with implicit acquisition of sequences (Bischoff-Grethe, Goedert, Willingham, & Grafton, 2004;Mayr, 1996;Willingham & GoedertEschmann, 1999;Willingham, Salidis, & Gabrieli, 2002). Given these prior findings, we think it improbable that explicit knowledge of the stimulus sequence interfered with implicit acquisition of the action sequence.…”
Section: Participants With Explicit Knowledgecontrasting
confidence: 99%
“…Given that the implicit group learned both location and action sequences, it is surprising that the explicit-locations group did not demonstrate learning the sequence of actions. This result conflicts with previous research that has demonstrated that explicit knowledge does not interfere with implicit acquisition of sequences (Bischoff-Grethe, Goedert, Willingham, & Grafton, 2004;Mayr, 1996;Willingham & GoedertEschmann, 1999;Willingham, Salidis, & Gabrieli, 2002). Given these prior findings, we think it improbable that explicit knowledge of the stimulus sequence interfered with implicit acquisition of the action sequence.…”
Section: Participants With Explicit Knowledgecontrasting
confidence: 99%
“…In some studies, dorsal PM has been reported to be specifically engaged in nonstandard mapping, referring to spatially incompatible mappings, in contrast to spatially compatible ones (Iacoboni et al, 1998;Bischoff-Grethe et al, 2004). Because spatial mapping is inherent to both compatible and incompatible mappings in these tasks, spatial mapping alone cannot account for stronger dorsal PM activation in incompatible mappings.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on training conditions, it is possible to demonstrate that participants are learning the perceptual ordering of stimuli in the task, the discrete motor responses in the task, or the outcome of the responses, that is, the distal goals or consequences of the action (Bapi, Doya, & Harner, 2000;Hazeltine, 2002). With SRT sequence learning there is typically increasing activity in supplementary motor area (SMA) or pre-supplementary motor area (pre-SMA) and the inferior parietal lobule (IPL) (Bapi, Miyapuram, Graydon, & Doya, 2006;Bischoff-Grethe, Goedert, Willingham, & Grafton, 2004;Grafton et al, 1995;Grafton, Hazeltine, & Ivry, 1998). At a single neuron level, coding for sequence order in a very small set of over-learned movements is observed in SMA in humans (Amador & Fried, 2004) and in monkeys within SMA, pre-SMA (Tanji, 1996;Tanji & Shima, 1994) and IPL as well as the motor cortex (Lu & Ashe, 2005) but not in regions associated with reaching (Batista & Andersen, 2001).…”
Section: Functional Imaging Studies Of Action Sequencingmentioning
confidence: 99%